NEW GENERATION ARCHITECTURE: INNOVATIONS, TECHNOLOGIES AND FUTURE DEVELOPMENT - Abdurahmonov Otabek Ravshan ogli (Bright Mind Publishing, 2024)
Modern architecture has been developing rapidly in recent years, combining ecological balance, technological innovations and smart infrastructures. This article analyzes the concept of new generation architecture, its main directions, ecological construction, smart cities, biomorphic design and the impact of artificial intelligence. It also discusses how the growth of urbanization and climate change will affect the development of architecture.